2017
DOI: 10.1111/bph.13933
|View full text |Cite
|
Sign up to set email alerts
|

Morin, a novel liver X receptor α/β dual antagonist, has potent therapeutic efficacy for nonalcoholic fatty liver diseases

Abstract: Our data reveal that morin is a dual antagonist of LXRα and LXRβ and suggest that morin may alleviate hepatic steatosis and other associated metabolic disorders via the suppression of LXR signalling and, therefore, shows promise as a novel therapy or nutraceutical for nonalcoholic fatty liver disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 64 publications
(68 reference statements)
3
19
0
Order By: Relevance
“…All analyses were performed using GraphPad Prism 6.0 (Graph Pad Software, San Diego, CA, USA; RRID:SCR_002798) or SPSS 19.0 software (IBM, Chicago, IL, USA; RRID:SCR_002865). Sample size of each protocol was determined on the basis of similar previous studies (Gu et al, 2017; Wang et al, 2017). Group size is the number of independent values and that statistical analysis was done using these independent values.…”
Section: Methodsmentioning
confidence: 99%
“…All analyses were performed using GraphPad Prism 6.0 (Graph Pad Software, San Diego, CA, USA; RRID:SCR_002798) or SPSS 19.0 software (IBM, Chicago, IL, USA; RRID:SCR_002865). Sample size of each protocol was determined on the basis of similar previous studies (Gu et al, 2017; Wang et al, 2017). Group size is the number of independent values and that statistical analysis was done using these independent values.…”
Section: Methodsmentioning
confidence: 99%
“…In this context, plant polyphenols are likely good candidates since several of these well‐known antioxidant compounds are now widely regarded as pharmacological agents that regulate target proteins and associated signalling pathways including in pancreatic beta cells (Dall'Asta et al, ; Goszcz, Duthie, Stewart, Leslie, & Megson, ; Oak et al, ; Saponara, Carosati, Mugnai, Sgaragli, & Fusi, ). The possibility of developing polyphenol‐based therapeutics is further supported by studies reporting that a number of polyphenols elicit therapeutic‐like effects at pharmacological micromolar concentrations in cells, tissues, and various animal models (Bai et al, ; Gu et al, ; Wright, ; Zhao et al, ). However and in contrast to the naturally occurring plant polyphenols, the bioactivity of their metabolite derivatives has more recently emerged and hence is still poorly characterized (Del Rio et al, ; Espín, Larrosa, García‐Conesa, & Tomás‐Barberán, ; Goszcz et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, MH, one of the most widely distributed flavonoids in plants, possesses strong free radical scavenging ability and potent hepatoprotective effects (Caselli et al, 2016; Lee et al, 2016; Naowaboot et al, 2016). Several studies in animal models have demonstrated that the administration of morin significantly prevented liver injury, inflammation, and fibrosis (Rizvi et al, 2015; Gu et al, 2017; Perumal et al, 2017; Tian et al, 2017; Li et al, 2018). For example, MH attenuated acetaminophen-induced liver injury by potentiating Nrf2 regulated survival mechanism (Rizvi et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…MH has been reported to possess antioxidant, neuroprotective, anti-inflammatory, antihypertensive, and anticancer properties (Dong et al, 2015; Caselli et al, 2016; Lee et al, 2016; Naowaboot et al, 2016). In particular, MH has also shown to inhibit liver injury, inflammation, and fibrosis in several different animal models by its antioxidant and anti-inflammatory effects (Rizvi et al, 2015; Gu et al, 2017; Perumal et al, 2017; Tian et al, 2017). However, the exact molecular mechanism underlying the hepatoprotective effect of MH is still partially understood.…”
Section: Introductionmentioning
confidence: 99%